Seasonal Hyperacute Panuveitis (SHAPU) - Gurung, Nanda Kumari (Journal of Nepalgunj Medical College, 2021)
Introduction SHAPU is a mysterious disease seen and reported only from Nepal since 1975. It is an important cause of unilateralchildhood blindness and is the most devastating intraocular inflammatory disease leading to loss of sight within a week. Although initially presented as a case report at a Nepal prevention of blindness meeting in 1978 and reported in national journal Malla O, editor Endophthalmitis probably caused by Tussock moth. Report of the preceding of the first National seminar on Prevention of Blindness: 1978.Upadhyan MP: Eye problems of Nepalese Children in 1979.Now there are more than 10 published articles available in the Website.